Future orientation buffers depression in daily and specific stress. Issue 3 (4th April 2019) - Zheng, Lei; Lippke, Sonia; Chen, Yidi; Li, Danyang; Gan, Yiqun
Abstract: Future orientation has been regarded as a protective factor that helps prevent problem behaviors, such as drug and alcohol use, smoking, and unprotected sex. Recently, many studies have focused on the relationship between a person's orientation towards the future and his or her depression symptoms; however, relatively few studies have explored the effect of future orientation on depressive responses to ordinary stress. The present study aimed to test whether future orientation could be a protective factor against depression in ordinary stress contexts. We conducted two studies to test this hypothesis and recruited 369 participants. Study 1 was a cross‐sectional study that involved 217 employees from a food‐processing company and examined the effect of future orientation in a daily stress context. Study 2 tested a hierarchical linear model in which 152 college students from an examination training institution in Beijing completed a five‐wave assessment with 3‐week intervals before taking the national entrance examination for postgraduate studies. The results showed that future orientation moderated the stress–depression relationship in the two samples. The present study provides evidence supporting the hypothesis that future orientation helps individuals cope with stress and protects people from depression, suggesting that future orientation plays a protective role in the stress–depression relationship.